2017
DOI: 10.5792/ksrr.16.034
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Literature on Culture-Negative Periprosthetic Joint Infection: Epidemiology, Diagnosis and Treatment

Abstract: PurposeThe prevalence of periprosthetic joint infection (PJI) has increased with the increasing incidence of arthroplasty surgery. Considering identification of causative microorganisms is crucial for treatment of PJI, culture-negative (CN) PJI is a significant clinical issue. The purpose of the present study is to describe epidemiology, diagnosis and treatment of CN PJI based on review of the literature to help prevent delayed diagnosis and improve clinical outcomes of CN PJI.MethodsMEDLINE, EMBASE, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 41 publications
3
83
0
5
Order By: Relevance
“…Therefore, we included cases from January 2016 to ensure the conformity of the two groups. Twenty-seven cases of CN-PJI cases (27.84%) were recorded among the 97 consecutive PJI cases during the study period, and this rate is similar to that reported in the literature [5,20]. This result reflects the actual situation at the PJI referral center to some extent.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, we included cases from January 2016 to ensure the conformity of the two groups. Twenty-seven cases of CN-PJI cases (27.84%) were recorded among the 97 consecutive PJI cases during the study period, and this rate is similar to that reported in the literature [5,20]. This result reflects the actual situation at the PJI referral center to some extent.…”
Section: Discussionsupporting
confidence: 86%
“…Due to pathogen encapsulation within biofilms [1], low microbial concentrations [2], the prior use of antibiotics [3], and the difficulty associated with the culturing of some pathogens [4], culture-negative prosthetic joint infection (CN-PJI) accounts for approximately 7-12% of all PJI cases [5]. The current guidelines and the consensus opinion recommend the use of empirical therapy with vancomycin and broad-spectrum beta-lactams (piperacillin/tazobactam or third-generation cephalosporins) for the treatment of CN-PJI [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Total knee arthroplasty is a common surgical procedure, and the most common reason for failure is infection, termed periprosthetic joint infection (3, 4). S. aureus periprosthetic joint infection can be culture negative for prolonged periods (5, 6), has high failure rates above 50% once treatment is initiated (5), and a 5-year mortality of 20% (79), higher than many common cancers (10). Similar to other surgical implant associated infections, the challenge in treating this disease involves the ability of S. aureus to develop a chronic biofilm associated infection tolerant to antibiotics (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…In the clinic, CN PJIs are not uncommon. It has been reported that the incidence of CN PJI is between 0% and 42.1% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Other surgical strategies include DAIR with replacement of the polyethylene insert, one-stage revision, permanent joint fusion, etc. 5 . A systemic combination of vancomycin and third-generation cephalosporins or carbapenems is the most commonly used regimen for CN PJI 5 .…”
Section: Introductionmentioning
confidence: 99%